Metabolic Characteristics of Lame Cows During Puerperium and the Beginning of the Reproductive Period - Anastasia Praxitelous; Panagiotis D. Katsoulos; Angeliki Tsaousioti; Marion Schmicke; Athina Basioura; Constantin M. Boscos; Georgios Tsousis (Ruminants)
This study presents findings from two discrete experimental processes that examined the impact of lameness events on two consecutive, critical time points in the annual production cycle of dairy cattle (early in puerperium—first study, and later at the onset of the reproductive period—second study) regarding liver function, glucose levels, milk production, body condition score, and back fat thickness. In the first study, 47 cows (lame group n = 22, control group n = 25) were monitored from 10 days ante partum (ap) to 46 days post-partum (pp). In the second study, 79 cows (lame group n = 52, control group n = 27) were monitored from day 28 ± 5 pp to day 65–72 ± 5 pp. Lame cows had greater gamma-glutamyl transferase (GGT) concentrations in the blood serum compared to control cows (25.83 vs. 23.56, p = 0.02, respectively) early in puerperium, whereas the two groups did not differ in the second study. The concentration of glutamate dehydrogenase (GLDH) was lower for lame compared to control cows in both studies (17.24 vs. 24.60, respectively, p = 0.02 in the first study, and 30.50 vs. 51.10, respectively, p = 0.02 in the second study). The concentrations of aspartate transaminase (AST) and glucose did not differ between groups in both studies. Lame cows had a lower body condition score (BCS) and backfat thickness (BFT) scores compared to the control in both studies overall. The lame cows of the first study experienced a significant loss of milk production, especially during the second month of lactation, while in the second study, milk production remained unaffected. Conclusively, lame cows have lower BCS and BFT values, whereas milk yield can be negatively affected only if lameness occurs early in the puerperium, probably beginning at the dry period. However, the current research shows that acutely lame cows, as described in this study, exhibit only mild alterations in liver function compared to non-lame ones.